Butterfly Hotels, Ltd. - a UK insolvency law and practice case study - Pond, Keith (Henry Stewart Talks, 2019)
Butterfly Hotels Ltd. as an “iceberg” case study, Financial overview of Butterfly Hotels Ltd.: External, internal and market factors, Management decisions and management actions influencing Butterfly Hotels’ fate